ANALISA KREDIT MACET PADA BANK UMUM MILIK NEGARA TERMASUK DALAM TINDAK PIDANA KORUPSI KERUGIAN KEUANGAN NEGARA - SJIN PHEN; suartini (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
This research focuses on the analysis of bad debts at state-owned commercial banks such as Bank Rakyat Indonesia (BRI), Bank Mandiri, Bank Negara Indonesia (BNI), Bank Tabungan Negara (BTN), and Bank Syariah Indonesia (BSI) which provide capital loans to their customers and due to Covid-19, economic conditions weaken so that bad debts occur. This bad credit condition turned out to have an impact on corruption crimes which resulted in state financial losses because the credit came from state-owned banks. This study takes a sample of corruption case number 39/Pid.Sus-TPK/2021/PN Jkt.Pst. According to Law Number 10 of 1998 concerning Banking, the definition of credit is the provision of money or bills that can be equated with it, based on an agreement or borrowing agreement between a bank and another party that requires the borrower to repay his debt after a certain period of time with interest. In the research on corruption case number 39/Pid.Sus-TPK/2021/PN Jkt.Pst, where there has been a restructuring of bad credit payments from BRI, namely the BRIGUNA product, which is a second stage loan where the first stage has been completed and due to the impact of Covid-19 there is congestion and the investigators declare it a corruption crime resulting in state financial losses because the credit comes from a state-owned bank. This research analyzes how the need for separation of rules regarding, especially in banking, the rules of criminal acts of corruption relating to state-owned commercial banks, due to the different views of banking law experts and judges regarding the rules of criminal acts of corruption relating to the problem of bad credit from state-owned commercial banks that have an impact on state financial losses as a criminal act of corruption is not criminal law but civil law.